Маркетингова політика розподілу підприємств сільськогосподарського машинобудування - Нехай, Вікторія Василівна; Нехай, Виктория Васильевна; Nekhai, Viktoriia (My University, 2018)
UK: Визначено напрямки оновлення методологічних засад маркетингового управління розподілом, що має сприяти розвитку підприємств. Вказано на необхідні зміни в організації та управлінні ринковими процессами, систематизовано комунікаційні заходи з просування продукції підприємств сільськогосподарського машинобудування. EN: The purpose of this article is to determine the main directions of formation and improvement of marketing policy of distribution in the activities of enterprises of agricultural machinery. The joint work of the scientists emphasizes the need to work out more effective methods of organizing separate units of distribution activity. The task of the methodology of scientific research in the marketing policy of distribution and in the activities of enterprises is important. It is necessary to find patterns of this process and ways to optimize it. Growth in sales of manufactured products is of great importance for business. Marketing distribution policies affect this process. There are tasks of full satisfaction of the buyer's requirements, need to use an individual approach. Communication measures to promote the production of agricultural machinery must take into account the features of the industry. It is necessary to know which industry is the consumer, the features of interaction with consumers, the specifics of the region of activity. This is reflected in each stage of the campaign. Marketing strategies of enterprises at different stages of the life cycle are different and individual. The components of marketing mix are defined in stages of the product life cycle. Marketing measures for agricultural machine-building enterprises have been developed. Thus, the strategies of agricultural machinery enterprises are defined at different stages of the life cycle. To determine the stage of the life cycle it is necessary to have the necessary information about the market situation, the position of the goods among such. Further study and practical application of approaches to developing the latest means of marketing distribution policy implementation will be required. Further study and practical application of approaches to developing the latest means of marketing distribution policy implementation will be required
Marketing policy of distribution of agricultural machine-building enterprises
Keywords: збут; маркетинг; просування продукції; ринок; розподіл; сільськогосподарське машинобудування; технічне забезпечення